2019
DOI: 10.1001/jamanetworkopen.2019.9441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bismuth Subsalicylate vs Placebo on Use of Antibiotics Among Adult Outpatients With Diarrhea in Pakistan

Abstract: IMPORTANCE Many of the 4.5 billion annual episodes of diarrhea are treated unnecessarily with antibiotics; prevalence of antibiotic resistance among diarrheal pathogens is increasing. Knowledgebased antibiotic stewardship interventions typically yield little change in antibiotic use. OBJECTIVE To compare antibiotic use among adult outpatients with diarrhea given bismuth subsalicylate (BSS) or placebo. DESIGN, SETTING, AND PARTICIPANTS This randomized clinical trial took place from April to October 2014. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…The microbiologic causes include parasitic (e.g., Giardia, Cryptosporidium, Schistosoma mansoni ) and bacterial (e.g., enteroaggregative E. coli, Shigella, Campylobacter, Salmonella ) pathogens [ 21 ]. BSS has demonstrated effectiveness in the prevention of traveler's diarrhea [ 112 , 113 ] and in the treatment of acute diarrhea [ 114 ]. For traveler's diarrhea in adult patients with mild symptoms [ 115 , 116 ], BSS has been shown to decrease stool frequency, time to symptom relief, need for intravenous rehydration, and work absenteeism in comparison to placebo or antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The microbiologic causes include parasitic (e.g., Giardia, Cryptosporidium, Schistosoma mansoni ) and bacterial (e.g., enteroaggregative E. coli, Shigella, Campylobacter, Salmonella ) pathogens [ 21 ]. BSS has demonstrated effectiveness in the prevention of traveler's diarrhea [ 112 , 113 ] and in the treatment of acute diarrhea [ 114 ]. For traveler's diarrhea in adult patients with mild symptoms [ 115 , 116 ], BSS has been shown to decrease stool frequency, time to symptom relief, need for intravenous rehydration, and work absenteeism in comparison to placebo or antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this drug has proven to be efficacious in both adults and children [82,83]. Moreover, a placebocontrolled randomized clinical trial demonstrated that patients with diarrhea who received bismuth subsalicylate have a reduced antibiotic consumption [84], which is an important finding concerning the actual problem of antibiotic resistance.…”
Section: Other Propertiesmentioning
confidence: 99%